6B.04: COMPLEMENT-INHIBITED PERIVASCULAR ADIPONECTIN EXPRESSION CONTRIBUTES TO VASCULAR INJURY IN HYPERTENSIVE MICE. (June 2015) - Ruan, C.; Ma, Y.; Li, Y.; Ge, Q.; Zhu, D.; Gao, P.
Abstract : Objective: Perivascular adipose tissue (PVAT) is implicated in the regulation of hypertensive vascular injury and our previous study showed that macrophage-derived complement 3 (C3) is involved. However, whether complements regulate PVAT-derived adipokines is still not clear. We conducted a gene chip analysis of adipokines in the PVAT from deoxycorticosterone acetate (DOCA)-salt hypertensive mice and control SHAM mice. C3 knockout (C3KO) mice or complement 5a (C5a) antagonist (AntiC5a) were used to blockade complement pathway in DOCA-salt hypertensive mice. Flow cytometry, Immunoflurenrescence and Western blot were performed to identify the adipokines expression in the PVAT of DOCA-salt mice. Design and method: We conducted a gene chip analysis of adipokines in the PVAT from deoxycorticosterone acetate (DOCA)-salt hypertensive mice and control SHAM mice. C3 knockout (C3KO) mice or complement 5a (C5a) antagonist (AntiC5a) were used to blockade complement pathway in DOCA-salt hypertensive mice. Flow cytometry, Immunoflurenrescence and Western blot were performed to identify the adipokines expression in the PVAT of DOCA-salt mice. Results: DOCA-salt treatment resulted in a decreased expression of adiponectin (APN) in the PVAT, which plays an anti-inflammatory role in cardiovascular disease. C3KO or AntiC5a treatment rescued APN expression in the PVAT of DOCA-salt mice. In vitro, although complement did not directly inhibit APN expression in 3T3-L1 adipocytes, C5a treated macrophage-conditioned medium inhibited APN expression. In addition, C5a-induced Tumor Necrosis Factor α (TNFα) in macrophage contributed to the decrease of APN in adipocytes. TNFα siRNA transfection in C5a-treated macrophages enhanced APN expression in adipocytes. In vivo, APN knockout blocked the protective role of AntiC5a in the DOCA-salt hypertensive mice accompanied with increased macrophage infiltration and inflammatory factor expression in the PVAT of DOCA-salt mice. Conclusions: These data suggest that the expression of PVAT-derived APN is decreased in hypertensive mice. Complement plays a role in the regulation of APN in the PVAT via macrophage-derived TNFα, which contributes to perivascular inflammation and vascular injury in the DOCA-salt hypertensive mice.